1961
DOI: 10.1002/ardp.19612940403
|View full text |Cite
|
Sign up to set email alerts
|

Neue Verbindungen mit bakterizider, fungizider und das Wachstum von Viren hemmender Wirkung II. Thiourethane

Abstract: 59,20 3,82 5,31 12,16 13,4R 59,46 4,25 5,46 12,42 13,35 66,34 7,28 5,95 13,63 6636 7,40 6,15 13,71 49,78 4,18 15,84 24,17 49,50 3,78 15,80 24,23 50,83 3,452 11,83 27,14 51,11 3,61 ll,69 27,09 62,13 5,74 7,25 16,59 61,90 5,68 7,29 16,60 294.166. Bd. 1961, N~. 4 Neue Ferbinduizgen niit bnkterizider, fungizider Wirkung II 209

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1963
1963
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Antifungal activity of 2-benzyl-6-diethylamino-4-phenyl-2H-1,3,5-thiadiazine-2-carboxylate In 2004, Rodriguez-Fernandez et al [83] synthesized a new 1,3,5-thiadiazine compound; 2-benzyl-6-diethylamino-4-phenyl-2H-1,3,5-thiadiazine-2-carboxylate (70), and investigated its antifungal activity against the fungus P. digitatum and S. cerevisiae. The molecular structure of compound (70) is shown in Fig.…”
Section: Thiadiazine Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal activity of 2-benzyl-6-diethylamino-4-phenyl-2H-1,3,5-thiadiazine-2-carboxylate In 2004, Rodriguez-Fernandez et al [83] synthesized a new 1,3,5-thiadiazine compound; 2-benzyl-6-diethylamino-4-phenyl-2H-1,3,5-thiadiazine-2-carboxylate (70), and investigated its antifungal activity against the fungus P. digitatum and S. cerevisiae. The molecular structure of compound (70) is shown in Fig.…”
Section: Thiadiazine Compoundsmentioning
confidence: 99%
“…Antifungal compounds with a 1,3,5-thiadiazine core Compounds containing a 1,3,5-thiadiazine core have been demonstrated to possess antifungal properties. It has become well established that the 1,3,5-thiadiazine-2-thione moiety exhibits antifungal activity through the production of isothiocyanate and dithiocarbamic acids [69][70][71][72][73][74][75][76][77][78] In 2001, Hussein et al [79] reported on several new derivatives of the 1,3,5-thiadiazine-2-thione core. The study was based on introduction of two moieties of 1,3,5-thiadiazine-2-thione through an ethylene bridge and investigation of the antifungal activity of these structural analogues.…”
Section: Thiadiazine Compoundsmentioning
confidence: 99%
“…The difficulty of preparation of such compounds might be attributed to the salt formation of 2-aminoethanol in strong alkaline medium [3]. …”
Section: Chemistrymentioning
confidence: 99%
“…It was suggested that the reaction proceeds through the formation of the intermediate (2) in situ [12][13][14][15] . Structures of the synthesized compounds were verified on the basis of spectral and elemental methods of analyses.…”
Section: Chemistrymentioning
confidence: 99%